Eficiência dos surfatantes de uso agrícola na redução da tensão superficial - Montório, Gilmar Aparecido [UNESP] (Universidade Estadual Paulista (Unesp), 2001)
O presente trabalho teve por objetivo avaliar a tensão superficial de soluções com diferentes surfatantes. Utilizaram 180 tratamentos combinados de forma fatorial (15x12), correspondendo a quinze surfatantes (Ag-Bem, Agral, Aterbane BR, Agrex, Break Thru, Extravon, Energic, Fixade, Gotafix, Haiten, Herbitensil, Iharaguem, Lanzar, Silwet L-77 e Wil Fix) e 12 concentrações (0; 0,001; 0,0025; 0,005; 0,01; 0,025; 0,05; 0,1; 0,25; 0,5%; 1 e 2%). A análise estatística dos dados foi realizada com auxilio do programa SAS e para análise de regressão, adotou-se o modelo de Mitscherlich com algumas modificações (Y = 72,6 - A .(1 - 10 - C . X )), onde “A” e “C” são constantes, “X” é a concentração e “Y” é a tensão superficial. A expressão “72,6 - A” corresponde a mínima tensão superficial que pode ser alcançada com o surfatante em questão. A tensão mínima alcançada com os surfatantes permite dispo-los na seguinte ordem crescente: Silwet (19,08 mN/m), Break Thru (19,87 mN/m), Wil Fix (24,71 mN/m), Haiten (27,94 mN/m), Fixade (28,23 mN/m), Agrex (29,29 mN/m), Iharaguem (29,55mN/m), Herbitensil (29,66 mN/m), Agral (30,46 mN/m), Extravon (30,47 mN/m), Energic (30,74 mN/m), Gotafix (30,91 mN/m), Lanzar (32,41mN/m), Aterbane (32,68 mN/m) e Ag-Bem (32,71mN/m). Pelo coeficiente de eficácia (constante “C” do modelo de Mitscherlich) na redução da tensão superficial, os surfatantes foram dispostos na seguinte ordem decrescente: Break Thru (169,81), Silwet (143,43), Fixade (89,28), Herbitensil (63,74), Aterbane (46,38), Iharaguem (36,11), Extravon (30,39), Energic (27,81), Agral (24,31), Gotafix (22,68), Haiten (21,28), Ag-Bem (11,24), Lanzar (8,61), Agrex (4,01) e Wil Fix (1,52). Desenvolveu-se um procedimento alternativo para se calcular o coeficiente de micelização, a partir das curvas de tensão superficial em função das concentrações dos surfatantes.

The objective of this research was to evaluate the static surface tension of solutions of the major surfactants used, in Brazil, as adjuvant in pesticide applications. It were considered 180 treatments arranged in a factorial scheme 15 x 12 with 15 surfactants (Break Thru, Silwet L 77, Fixade, Herbitensil, Aterbane, Iharaguem, Extravon, Energic, Agral, Gotafix, Haiten, Ag- Bem, Lanzar, Agrex e Wil Fix) and 12 concentrations v/v (0; 0,001; 0,0025; 0,005; 0,01; 0,025; 0,05; 0,1; 0,25; 0,5%; 1 e 2%). It were performed regression analysis and established models relating surfactant concentration to the surface tensions. The model best fitted to the data was Y = 72,6 - A.(1 - 10 - C . X )), corresponding to a modification of Mitscherlich model, where Y is the surface tension, X is the concentration of the surfactant, A and C are constants of the model. The expression “72,6 - A” is the minimum surface tension that could be achieved by the use of a certain surfactant and “C” was named efficacy coefficient and refers to the potential of each product in reducing the surface tension. The organosilicon surfactants were the most effective in reducing surface tension. The minimum tensions that could be achieved were 19,08 mN/m and 19,87 mN/m respectively for Silwet L 77 and Break-thru. The efficacy coefficients for both products were 143,43 and 169,81, also in a respective way. The other 13 non-organosilicon surfactants could be ranked in the following increasing order of minimum surface tensions: Wil Fix (24,71 mN/m), Haiten (27,94 mN/m), Fixade (28,23 mN/m), Agrex (29,29 mN/m), Iharaguem (29,55mN/m), Herbitensil (29,66 mN/m), Agral (30,46 mN/m), Extravon (30,47 mN/m), Energic (30,74 mN/m), Gotafix (30,91 mN/m), Lanzar (32,41mN/m), Aterbane (32,68 mN/m) and Ag-Bem (32,71mN/m). Considering the efficacy coefficients, the surfactants could be disposed in the following decreasing order... (Complete abstract, click electronic address below).
Keywords: Tensão superficial; Surfatante - Uso agrícola; Surfactants